2010
DOI: 10.1103/physrevlett.105.193603
|View full text |Cite
|
Sign up to set email alerts
|

Cooperative Atom-Light Interaction in a Blockaded Rydberg Ensemble

Abstract: We demonstrate a cooperative optical non-linearity caused by dipolar interactions between Rydberg atoms in an ultra-cold atomic ensemble. By coupling a probe transition to the Rydberg state we map the strong dipoledipole interactions between Rydberg pairs onto the optical field. We characterize the non-linearity as a function of electric field and density, and demonstrate the enhancement of the optical non-linearity due to cooperativity. PACS numbers: 42.50.Nn, 32.80.Rm, 34.20.Cf, 42.50.Gy Photons are robus… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

14
647
1
3

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 483 publications
(665 citation statements)
references
References 48 publications
14
647
1
3
Order By: Relevance
“…To maintain strong two-photon suppression in the presence of diffusion, the loss term must exceed the diffusion on the length scale of the blockade radius, requiring r b > l a . Large optical depth OD b = r b /l a of the blockaded region is therefore the key experimental feature that allows us to extend earlier studies 13 into the quantum nonlinear regime.…”
mentioning
confidence: 82%
See 2 more Smart Citations
“…To maintain strong two-photon suppression in the presence of diffusion, the loss term must exceed the diffusion on the length scale of the blockade radius, requiring r b > l a . Large optical depth OD b = r b /l a of the blockaded region is therefore the key experimental feature that allows us to extend earlier studies 13 into the quantum nonlinear regime.…”
mentioning
confidence: 82%
“…The most promising approaches have used high-finesse optical cavities to enhance the atom-photon interaction probability 2,[17][18][19][20][21] . In contrast, our present method is cavity-free and is based on mapping photons onto atomic states with strong interactions in an extended atomic ensemble 13,14,22,23 . The central idea is illustrated in Fig.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Our approach is to couple a light field propagating in a dispersive medium to highly excited atomic states with strong mutual interactions (Rydberg states) 13,14 . Similar to previous studies of quantum nonlinearities via Rydberg states that were based on dissipation [15][16][17][18][19] rather than dispersion 20 , we make use of electromagnetically induced transparency (EIT) to slow down the propagation of light 21 in a cold atomic gas. By operating in a dispersive regime away from the intermediate atomic resonance (Fig.…”
mentioning
confidence: 99%
“…It has recently been shown that even weak optical nonlinearities between single photons can be used to perform important quantum communication tasks more efficiently than methods based on linear optics 2 , which have fundamental limitations 3 . Nonlinear optical effects at single-photon levels in atomic media have been studied 4,5 and demonstrated [6][7][8][9] , but these are neither flexible nor compatible with quantum communication, as they impose restrictions on photons' wavelengths and bandwidths. Here we use a high-efficiency nonlinear waveguide (WG) 10,11 to observe the sum-frequency generation (SFG) between a single photon and a single-photon level coherent state from two independent sources.…”
mentioning
confidence: 99%